The Middle Length Discourses of the Buddha - A New Translation of the Majjhima Nikaya. Translated by Bhikkhu Ñanamoli and Bhikkhu Bodhi. - Mills, Laurence C. R. (Buddhist Studies Review, 1997)
The Middle Length Discourses of the Buddha - A New Translation of the Majjhima Nikaya. Translated by Bhikkhu Ñanamoli and Bhikkhu Bodhi. Wisdom Publication, Boston, Mass., 1995. 1412 pp. (Preface & Introduction 13-60, Summaries 61-75, Translation 83-1151, Bibliography, Abbreviations, Notes, Glossary, Index 1155-1412). US$75.00. ISBN 0-86171-072-X.